Correlation Between CASC8, SMAD7 Polymorphisms and the Susceptibility to Colorectal Cancer: An Updated Meta-Analysis Based on GWAS Results. Issue 46 (November 2015) - Yao, Kunhou; Hua, Long; Wei, Lunshou; Meng, Jiming; Hu, Junhong
Abstract : Abstract: Genome-wide association studies (GWASs) and a number of case–control studies have suggested that several single nucleotide polymorphisms (SNPs), rs7837328, rs7014346, rs6983267, rs10505477 on CASC8 gene and rs4939827, rs4464148, rs12953717 on SMAD7 gene are significantly correlated with the susceptibility to colorectal cancer (CRC). For the sake of clarifying the association, a meta-analysis was conducted and population heterogeneity was considered in the study. A total of 34 articles including 90 studies (168, 471 cases and 163, 223 controls) that evaluated the relationship between the CASC8, SMAD7 genes and the risk of CRC under the allelic model were reviewed. Also subgroup analysis was performed by ethnicity (Caucasian, Asian, and African) and all of the analyses were implemented in R 3.2.1 software. Pooled data from the meta-analysis revealed that the A allele of rs7837328, the A allele of rs7014346, the G allele of rs6983267, the A allele of rs10505477, the T allele of rs4939827, the T of rs4464148, and the T of rs12953717 were significantly associated with an increased risk of CRC under the allelic model. Additionally, subgroup analyses of 6 SNPs by ethnicity (rs4464148 excepted) witnessed that the A allele of rs7837328, the G allele of rs6983267, and the T of rs12953717 were notably associated with an increased risk of CRC among Caucasian and Asian. Furthermore, the A allele of rs7014346, the A allele of rs10505477, and the T allele of rs4939827 were significantly related with an elevated risk of CRC only among Caucasian. Our study suggested that for CASC8 gene, SNP of rs7837328 and rs6983267 are risk factors for CRC among both Caucasian and Asian whereas rs7014346 and rs10505477 are risky gene polymorphisms only among Caucasian. For SMAD7 gene, rs4939827 and rs4464148 are risk factors for CRC among Caucasian whereas rs12953717 could elevate the susceptibility to CRC in both Caucasian and Asian.